Detonation Characteristics of an Aluminized DNAN‐Based Melt‐Cast Explosive. Issue 1 (24th August 2022) - Yang, Yang; Duan, Zhuoping; Li, Shurui; Han, Yong; Huang, Hui; Zhang, Liansheng; Huang, Fenglei
Abstract: Investigations of the detonation characteristics of a new aluminized DNAN‐based melt‐cast explosive RMA‐2X (containing 30 wt.% DNAN (2, 4‐dinitroanisole), 30 wt.% NTO (3‐nitro‐1, 2, 4‐triazol‐5‐one), 10 wt.% HMX (1, 3, 5, 7‐tetranitro‐1, 3, 5, 7‐tetraazacyclooctane) and 30 wt.% aluminum) were undertaken, as well as a lithium fluoride (LiF) substituted explosive RMF‐2X (containing 30 wt.% DNAN, 30 wt.% NTO, 10 wt.% HMX and 30 wt.% LiF). The interfacial velocity experiment was carried out to measure the reaction zone parameters (including the CJ pressure, the pressure at the Von Neumann spike, and the reaction zone length) of RMA‐2X. The cylinder test was also performed, and employing the test data, the detonation velocity, the Gurney energy, and the detonation energy of RMA‐2X were calculated. Investigation results are analyzed and some conclusions are drawn. The role of aluminum in the detonation characteristics are also discussed. Finally, parameters of the Jones‐Wilkins‐Lee equation of state of the detonation products were confirmed. Abstract :